Figure 2 from: Abdul Kadir SR, Abdul Rasid MHF, Kwong KO, Wong LL, Arai T (2017) Occurrence and the ecological implication of a tropical anguillid eel Anguilla marmorata from peninsular Malaysia. ZooKeys 695: 103-110. https://doi.org/10.3897/zookeys.695.13298 - Abdul Kadir, Siti Raudah; Abdul Rasid, Mohamad Hafiz Farhan; Kwong, Kok Onn; Wong, Li Lian; Arai, Takaomi (Zenodo, 2017)
Figure 2 - Anguilla marmorata and A. bengalensis bengalensis collected in the Pondok Upeh River in Penang Island of Peninsular Malaysia. A Anguilla marmorata (904 mm in TL) B Anguilla bengalensis bengalensis (889 mm in TL) C Wide maxillary bands of teeth of A. marmorata D Narrow maxillary bands of teeth of A. bengalensis bengalensis. DNA was extracted from dorsal fin clip of each specimen, and hence the posterior dorsal fin of each specimen is lacking.